PENGARUH ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA: PERAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Triyani, Oetary; Junita, Dewi; Cahayani Adha, Afifah; Safitri, Yulia; Sufanda, Zerry (LPPM Universitas Awal Bros, 2023)
This research aims to examine the effect of information asymmetry on earnings management with corporate governance as a moderating variable. Bid-Ask Spread is used to measure information asymmetry variables. Discretionary accruals are used to measure earnings management. The proportion of independent board of commissioners, proportion of institutional ownership, proportion of managerial ownership, and number of audit members are used to measure the effectiveness of corporate governance. The population of this research was 139 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 so that from this population a sample of 34 companies was obtained using the purposive sampling method. The data analysis technique used in this research is the Moderated Regression Analysis (MRA) interaction test. The research results show that information asymmetry has no effect on earnings management, an independent board of commissioners, institutional ownership and audit committee can moderate the effect of information asymmetry on earnings management, while managerial ownership cannot moderate the effect of information asymmetry on earnings management.